Implementation of performance-based capitation payment at public health centers in Denpasar, Bali, Indonesia - rosida, Anik; Ni Made Sri Nopiyani; Pande Putu Januraga (Public Health and Preventive Medicine Archive, 2024)
Background and purpose: The National Health Insurance System has implemented a performance-based capitation (PBC) norm in primary health care facilities (PHCF). PBC has three indicators: contact rate, non-specialist referral ratio (NSRR), and controlled chronic diseases control program (Prolanis) participant ratio (CPPR). This study aims to explore the implementation of PBC payment at public health centers in Denpasar, Bali, Indonesia. Methods: This study utilizes an explanatory sequential mixed method design. Data collection was conducted from February to March 2023. In the first phase, quantitative data were gathered through documentation studies on PBC achievements. The second phase involved qualitative data collection through in-depth interviews with 11 informants, who were selected purposively. Thematic analysis was employed to identify internal and external factors hindering and driving PBC fulfillment. Results: Among the 11 public health centers in Denpasar, two met the PBC target in 2020, three in 2021, and seven in 2022. During 2020 to 2022, the NSRR and contact rate targets were achieved by all public health centers, except for the contact rate in 2021. The CPPR was the indicator with the lowest achievement, but shows an increasing trend. Strengths contributed to PBC's achievement including sufficient human resources and service facilities, an active Prolanis club, and a supportive Primary Care (P-Care). Weaknesses include the absence of planning documents, lack of capitation service reward, insufficient availability of medicines, and inadequate features of e-Puskesmas. Threats were suboptimal condition of Prolanis participants, the COVID-19 pandemic, non-specialist referral demands from patients, and increased number of target population. Conclusion: The achievement of PBC at public health centers in Denpasar from 2020 to 2022 was suboptimal. The emergence of various factors namely strengths, weaknesses, opportunities and threats, can be utilized in strategic formulation to optimize PBC in Denpasar public health centers.